The path through: Early COVID-19 job loss and labour market trajectories in Austria - Stefan Jestl; Maryna Tverdostup (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper examines the socio-demographic disparities evident in the early labour market response to the COVID-19 pandemic in Austria, relying on the register-based labour market career dataset from the Austrian Micro Data Center (AMDC) for the 2018-2021 period. The analysis focuses on the divergences in out-of-unemployment transitions and medium-term employment stability among those who lost their jobs early in the pandemic in contrast to the group of the longer-term unemployed. We document that individuals affected by job loss during the initial phases of the pandemic did not exhibit enduring scarring effects. Unlike their longer-term unemployed counterparts, they did not demonstrate persistent labour market detachment, prolonged periods of unemployment or a diminished success rate in reemployment. However, certain socio-demographic cohorts - notably, women, parents with two or more young children, and individuals with lower levels of education - faced disproportionate challenges during the pandemic. They were more inclined to transition into precarious employment arrangements and experienced lower levels of employment stability in the months following re-employment.
Keywords: E24; J16; J21; I24; 330; COVID-19; employment stability; gender inequalities; labour market transitions; unemployment